2018
DOI: 10.23736/s0375-9393.18.12697-6
|View full text |Cite
|
Sign up to set email alerts
|

μ-opioid receptor genetic polymorphisms and duration of epidural fentanyl analgesia during early labor

Abstract: OPRM1 SNVs did not affect the duration of epidural fentanyl administered for early labor analgesia in nulliparous women. These results should be confirmed in patients receiving epidural opioids in other clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…It is not permitted to frame or use framing techniques to enclose any trademark, logo, or other proprietary information of the Publisher. nulliparous women undergoing epidural fentanyl analgesia for labor; the authors found no difference in pain intensity, analgesia duration, side effects, and patient satisfaction in relation to three genetic polymorphisms: oPrM1 118a>g, ivs2+31g>a, and ivs2+691g>c. 140 the intraoperative use of opioids can affect the degree of postoperative analgesia by inducing hyperalgesia and tolerance. 141 Many studies showed that the n-methyl-D-aspartate receptor (nMDa) antagonist, ketamine is useful for both primary and secondary hyperalgesia after a variety of surgical procedures.…”
Section: Copyright © 2019 Edizioni Minerva Medicamentioning
confidence: 99%
“…It is not permitted to frame or use framing techniques to enclose any trademark, logo, or other proprietary information of the Publisher. nulliparous women undergoing epidural fentanyl analgesia for labor; the authors found no difference in pain intensity, analgesia duration, side effects, and patient satisfaction in relation to three genetic polymorphisms: oPrM1 118a>g, ivs2+31g>a, and ivs2+691g>c. 140 the intraoperative use of opioids can affect the degree of postoperative analgesia by inducing hyperalgesia and tolerance. 141 Many studies showed that the n-methyl-D-aspartate receptor (nMDa) antagonist, ketamine is useful for both primary and secondary hyperalgesia after a variety of surgical procedures.…”
Section: Copyright © 2019 Edizioni Minerva Medicamentioning
confidence: 99%
“…Ropivacaine is widely used in obstetric anesthesia due to its good analgesic properties while without resulting in motor blockade or systemic toxicity 10,11 . Fentanyl is an appropriate analgesic drug in use for labor because of its low molecular weight and high potency 12 . Some nonpharmacological pain management techniques include breathing techniques, water use, acupuncture/acupressure, massage, hypnotherapy, as well as transcutaneous electrical nerve stimulation (TENS) machine 13 .…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 Fentanyl is an appropriate analgesic drug in use for labor because of its low molecular weight and high potency. 12 Some nonpharmacological pain management techniques include breathing techniques, water use, acupuncture/acupressure, massage, hypnotherapy, as well as transcutaneous electrical nerve stimulation (TENS) machine. 13 TENS machine relieves pain by activating descending inhibitory systems of the central nervous system with a low‐voltage electrical current.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, one branch of pain research focuses on single nucleotide polymorphisms (SNPs) in acute and inflammatory pain as potential objective pain markers. SNPs can act as predictors of pain intensity and may indicate an increased need for opioid analgesics in the perioperative period [17,18]. One potential SNP associated with differences in pain perception and opioid requirements is the A118G SNP in the mu-opioid receptor 1 (OPRM1) gene.…”
Section: Introductionmentioning
confidence: 99%